THE INFLUENCE OF WORK DISCIPLINE AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT THE SAVINGS AND LOAN COOPERATIVE IN BOGOR REGENCY - Fathan Arif; Retno Japanis Permatasari (International Journal Multidisciplinary Science, 2024)
This study investigates the influence of work discipline and the physical work environment on employee performance at the Savings and Loan Cooperative in Bogor Regency. Recognizing the cooperative’s strategic role in the Indonesian economy, particularly in supporting member welfare, this research emphasizes the need for effective human resources. Work discipline and a conducive physical work environment are essential factors contributing to employee productivity. A quantitative approach was employed, with a saturated sampling technique applied to a population of 70 employees. Data was collected via a questionnaire that was validated and tested for reliability, ensuring the accuracy of the measurements. Statistical tests, including multiple linear regression and classical assumption testing, were utilized to analyze the data. Results indicate that both work discipline and the physical work environment positively and significantly impact employee performance, individually and collectively. The findings highlight the importance of maintaining high work discipline and optimizing the work environment to enhance employee performance. These insights serve as valuable guidance for cooperative management in establishing policies that foster a disciplined and supportive workplace conducive to achieving organizational goals.